Taxing carbon as an instrument of green industrial policy in developing countries - Anna Pegels (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Two simultaneous and interdependent issues challenge today's development policy: poverty reduction and climate change. While economic growth is needed to tackle poverty reduction, governments need to set economic frameworks and incentive systems so that this growth remains within global environmental boundaries. When designed well, many of these measures can contribute to alleviating poverty and fostering competitiveness – that is, they can be used as green industrial policy measures. This study focuses on carbon taxes as one possible green industrial policy instrument. It reviews existing evidence on competitiveness, employment and distributional effects with a view to informing the decisions of policymakers and bureaucrats in developing and emerging countries. To this aim, it pays particular attention to tax design options aimed at mediating negative and generating positive effects. Carbon taxes have several advantages for developing and emerging countries. First and foremost, they provide a good tax base and raise revenues which in turn can be used to support social and economic aims. Their technical implementation is relatively easy and they send stable price signals, especially when compared to cap and trade schemes. Lastly, when formal and informal companies alike have to pay, carbon taxes reduce incentives for firms to remain in the informal sector. Despite these advantages, only few developing and emerging countries have introduced or are considering introducing carbon taxes. One of the main reservations is the risk of negative impacts on economic and social aims. Ex post studies of competitiveness impacts in industrialised countries suggest that carbon or energy taxes have had neutral or even positive effects on competitiveness and gross domestic product (GDP). The studies also show that impacts depend crucially on the use of revenues. To have similarly positive effects in developing countries, however, carbon taxes may have to be designed differently. After all, these countries have different administrative capacities, economic structures and abilities to adapt to carbon pricing. In particular, distributive and poverty effects need consideration as they impact on the optimal use of tax revenues. Tax revenues could, for example, be used for direct transfers or the cross-subsidisation of electricity lifeline tariffs to protect people living in poverty from the negative impacts of carbon pricing. Furthermore, empirical studies suggest that revenue recycling to subsidise basic goods, such as food, can have positive effects on poverty.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Klimawandel